PENGARUH MEDIA MONOPOLI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA TEMA 3 SUBTEMA 2 DI KELAS VI SEKOLAH DASAR - Nainggolan, Beta Glorima; Lubis, Wildansyah; Irsan, Irsan; Prawijaya, Septian; Siregar, Fajar Sidik (Universitas Negeri Medan, 2024)
This research aims to determine the effect of monopoly media on student learning outcomes in theme 3 subtheme 2 in class VI of SDN 101777 Saentis. The research method used is quasi-experimental or quasi-experimental with a quantitative approach. The sample in this study was class consisting of 51 student. The research instrument used was a test instrument consisting of 21 multiple choice questions. Based on the result of data analysis, the average pretest score for the experimental class was 48 and the control class was 48, while the average posttest score for the experimental class was 84 so that the application of monopoly media can improve student learning outcomes. Based on this, it can be concluded that there is a significant influence from using monopoly media. Keywords: monopoly media, thematic, learning outcomes